2017
DOI: 10.1177/1539449217727119
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Social Isolation Among Urban Aging Adults: Informing Occupation-Based Approaches

Abstract: Socially isolated aging adults are at risk of poor health and well-being. Occupational therapy can help address this issue; however, information is needed to guide such work. National surveys characterize social isolation in populations of aging adults but fail to provide meaningful information at a community level. The objective of this study is to describe multiple dimensions of social isolation and related factors among aging adults in diverse urban neighborhoods. Community-based participatory research invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
(71 reference statements)
0
16
1
Order By: Relevance
“…Secondly, our study found that about 1.2% of patients with prostate cancer had social isolation mention(s) in their clinical narratives; this finding is consistent with a prior study, which reported that 1.2% of elderly adults were subjectively isolated (based on an individual’s perceptions about quality of his/her social relationship), and 5% of elderly adults were objectively isolated (through physical separation from and insufficient interaction with other people) [23]. However, other studies have estimated a 15–40% prevalence of social isolation among elderly adults, without reliance on a consensus definition and operationalization of social isolation [25]. Therefore, the true prevalence of social isolation in our study population is uncertain without access to confirmation from other measurements; notably unknown is the extent to which social isolation information is commonly recorded in providers’ clinical notes.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, our study found that about 1.2% of patients with prostate cancer had social isolation mention(s) in their clinical narratives; this finding is consistent with a prior study, which reported that 1.2% of elderly adults were subjectively isolated (based on an individual’s perceptions about quality of his/her social relationship), and 5% of elderly adults were objectively isolated (through physical separation from and insufficient interaction with other people) [23]. However, other studies have estimated a 15–40% prevalence of social isolation among elderly adults, without reliance on a consensus definition and operationalization of social isolation [25]. Therefore, the true prevalence of social isolation in our study population is uncertain without access to confirmation from other measurements; notably unknown is the extent to which social isolation information is commonly recorded in providers’ clinical notes.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapy research encourages practitioners to address injustices by identifying client strengths, identifying socially-structured inequalities, and advocating for the occupational rights of all people (Hammell, 2015;World Federation of Occupational Therapists, 2006). With a firm understanding of the value and the impact of occupational engagement on health and a clear role in client advocacy, occupational therapists are well-suited to address this issue by providing physical, social, and mental health services to low income populations (Hand, 2017).…”
Section: Low Income and Occupationmentioning
confidence: 99%
“…In this study, surveillance methods were used to identify needs for both population-level and individual-level interventions. Hand and colleagues (2017) used health surveillance methods to explore social isolation among aging adults in socioeconomically, racially, and ethnically diverse neighborhoods. They partnered with members of a community-based participatory research collective to survey community-dwelling older adults about their social isolation and factors related to social isolation.…”
Section: Health Surveillancementioning
confidence: 99%
“…There are a growing number of occupational therapy resources and tools designed for practitioners who want to add health surveillance methods and community-centered approaches to their practice (Hyett, McKinstry, Kenny, & Dickson-Swift, 2016). This special issue on occupational therapy and public health highlights research that demonstrates the occupational therapy lens in health surveillance (Hand et al, 2017; Peachey, Wenos, & Baller, 2017), community-centered programs (Coker-Bolt et al, 2017; Hyett, Kenny, & Dickson-Swift, 2017), and health disparities or inequities (Barnekow et al, 2017; Douglas, Benevides, & Carretta, 2017; Williamson, Conteras, Rodriquez, Smith, & Perkins, 2017).…”
mentioning
confidence: 99%